Continuous sugarcane cropping and chemical modifications of a Fragiudult - Maia, Joselanne Luiza Trajano; Ribeiro, Mateus Rosas (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this experiment was to evaluate the modifications on the chemical properties of a Fragiudult caused by continuous sugarcane cropping. In the same flat topographic position, three sites were selected, involving a native forest and sugarcane fields cultivated for periods of two and thirty years. The soils were morphologically characterized and samples were taken from each horizon to determine pH (H2O and KCl), organic carbon, extractable phosphorus, exchangeable bases, cation exchange capacity, base saturation and aluminum saturation. The soil management adopted in the sugarcane cropping led to significant reduction of calcium, magnesium, base saturation, cation exchange capacity and organic carbon, and increased phosphorus and aluminum saturation.
Keywords: chemical properties; continuous cropping; sugarcane